La Red de maestros animadores de la lectura y la escritura. - Gómez Jiménez, Roberto; Pérez Vega, Ma. de los Ángeles; Ruiz, Carmen; Pulido Ochoa, Roberto; Gonzáles Nicólas., Rigoberto (Nodos y Nudos, 2004)
NA